Integrated teaching in medical education: undergraduate student’s perception - Neeli, Divyasree; Prasad, Uma; Atla, Bhagyalakshmi; Kukkala, Saraswati Sarat Srinivas; Konuku, Venkata Bala Saikumar; Mohammad, Arfathunnisa (International Journal of Research in Medical Sciences, 2019)
Background: Integrated teaching is an effective teaching method for the undergraduate medical students to achieve good knowledge and skills. The aim of this study was to evaluate the effectiveness of vertical integrated teaching. Method: Vertical integrated teaching was conducted on the topic “Nephrotic syndrome” for 2nd MBBS (5th semester) students. Departments which participated in the session were from Physiology, Biochemistry, Pathology and General Medicine. Faculty from each department was allotted 20 minutes for their topic. After completion of all the topics students were given feedback forms. The opinions were tabulated and analysed. Results: Most of the students opined that integrated teaching is useful in gaining knowledge (Understanding, concept clarity and better performance in exams) (79.7%) as well as skill-based learning (Workshops, laboratory, clinical exercises and case discussion) (84.4%). Conclusion: The study showed that undergraduate students agreed that integrated teaching is useful for them in gaining knowledge as well as skill.